2022
DOI: 10.3389/fnagi.2022.982154
|View full text |Cite
|
Sign up to set email alerts
|

The hotspots and publication trends in postoperative delirium: A bibliometric analysis from 2000 to 2020

Abstract: BackgroundPostoperative delirium (POD) is a common aging-associated postoperative complication that has received increasing attention in the context of the aging global population and the number of articles published on POD is gradually increasing. This study aimed to quantify the basic information of scholarly publications on POD and identify the most impactful literature, trends, and hotspots in POD research.Materials and methodsWe searched articles on POD through the Science Citation Index Expanded database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The United States of America (USA) was the most productive country with 54 top-100 cited articles (Table 3). Germany ranked second ( 13), followed by Canada ( 9), the United Kingdom (UK) (7), China (7), Denmark ( 6), and the Netherlands (6) (Table 3). The top-10 institutions of publication counts are presented in Figure 3A.…”
Section: Country/region and Institutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States of America (USA) was the most productive country with 54 top-100 cited articles (Table 3). Germany ranked second ( 13), followed by Canada ( 9), the United Kingdom (UK) (7), China (7), Denmark ( 6), and the Netherlands (6) (Table 3). The top-10 institutions of publication counts are presented in Figure 3A.…”
Section: Country/region and Institutionmentioning
confidence: 99%
“…A bibliometric analysis of POD was published last year, in which studies from 2000-2020 were included. 7 However, a number of novel articles emerged after 2020, including top studies published in JAMA, JAMA Surgery, and the British Journal of Anesthesiology. [8][9][10] These studies not only provide vital guidance on practice but also bring new hotspots in the POD field.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative delirium (POD) is a prevalent and serious complication marked by acute and varying alterations in mental condition, attentional capabilities, and consciousness levels following liver resection [6][7][8] . Studies have shown a correlation between POD and unfavorable consequences, including heightened mortality rates, extended hospital stays, and elevated medical costs.…”
Section: Development Of An Individualized Model For Predicting Postop...mentioning
confidence: 99%
“…Until now, there have been abundant original investigations and secondary studies focusing on the mechanisms, risk factors, prediction, prevention, and treatment of POD. A bibliometric analysis of POD was published last year, in which studies from 2000-2020 were included [7] . However, a number of novel articles emerged after 2020, including top studies published in JAMA, JAMA Surgery, and the British Journal of Anesthesiology [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%